Pelatihan Produksi Teh Celup Herbal Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) dengan Pemanis Alami dari Daun Stevia pada Kelompok PKK Kelurahan Paropo Kota Makassar - Ira Asmaliani; Sukmawati; Andi Faisal Bahari (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
Pandan Wangi (Pandanus amaryllifolius Roxb.) is the only species of Pandan with fragrant leaves. From various studies, it is known that Pandan Wangi leaves have properties in maintaining and improving health, including antihyperglycemic and antinephrotoxicity. This plant is one of the potential biological resources that has been developed by the people of Paropo sub-district by making ketupat shells. In fact, innovative products such as fragrant pandan tea might add sales value and be good for health. This PKM aims to create new products from the local pandan fragrant plant with a focus on the production of pandan fragrant herbal tea bags with the natural sweetener stevia leaves, so that customers' buying interest in this product increases. The target partners for this service are the Paropo Village PKK group, totaling 20 people who are trying to be more productive. Apart from that, this service activity also teaches partners financial management by doing simple bookkeeping. This activity is carried out with the assistance of partners using Community Development, educational, persuasive and participatory methods.